Land Reform in Zimbabwe: a Balance of Political Expediency and Economic Inevitability? - PROKOPENKO Liubov Yaroslavovna (Ученые записки Института Африки Российской академии наук)
The article considers the political aspect of land reform in the Republic of Zimbabwe. The problem of land reform has been one of the crucial ones in the history of this African country, which celebrated 40 years of independence on April 18, 2020. In recent decades, it has been constantly in the spotlight of political and electoral processes. The land issue was one of the key points of the political program from the very beginning of Robert Mugabe’s reign in 1980. The political aspect of land reform began to manifest itself clearly with the growth of the opposition movement in the late 1990s.